Speech Strategy in Sentilan Sentilun Episode "Selangkah Menuju RI 1" on Metro TV (Critical Discourse Analysis) - Nur Sekhudin (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study discusses speech through critical discourse analysis (CDA) on Sentilan Sentilun Episode "Selangkah Menuju RI 1" in Metro TV with qualitative descriptive analysis method. This study aims to show the form of speech that is communicated, so speech strategies are found that are used to criticize. The critical discourse analysis (CDA) results show that Sentilan Sentilun Episode "Selangkah Menuju RI 1" in Metro TV describes the events to convey the message and display its participants. The speech strategy often used is indirect speech compared to direct speech. That is related to the delivery of conversational implicature in the form of criticism. Thus, it can be said that the participants on Sentilan Sentilun Episode "Selangkah Menuju RI 1" in Metro TV are seen using expressive strategies through what is felt by the speaker to convey the implications of the conversation in the form of criticism.